Chemical Pretreatment-Independent Saccharifications of Xylan and Cellulose of Rice Straw by Bacterial Weak Lignin-Binding Xylanolytic and Cellulolytic Enzymes - Teeravivattanakit, Thitiporn; Baramee, Sirilak; Phitsuwan, Paripok; Sornyotha, Somphit; Waeonukul, Rattiya; Pason, Patthra; Tachaapaikoon, Chakrit; Poomputsa, Kanokwan; Kosugi, Akihiko; Sakka, Kazuo; Ratanakhanokchai, Khanok (Applied and environmental microbiology, 2017)
Complete utilization of carbohydrate fractions is one of the prerequisites for obtaining economically favorable lignocellulosic biomass conversion. This study shows that xylan in untreated rice straw was saccharified to xylose in one step without chemical pretreatment, yielding 58.2% of the theoretically maximum value by Paenibacillus curdlanolyticus B-6 PcAxy43A, a weak lignin-binding trifunctional xylanolytic enzyme, endoxylanase/β-xylosidase/arabinoxylan arabinofuranohydrolase. Moreover, xylose yield from untreated rice straw was enhanced to 78.9% by adding endoxylanases PcXyn10C and PcXyn11A from the same bacterium, resulting in improvement of cellulose accessibility to cellulolytic enzyme. After autoclaving the xylanolytic enzyme-treated rice straw, it was subjected to subsequent saccharification by a combination of the Clostridium thermocellum endoglucanase CtCel9R and Thermoanaerobacter brockii β-glucosidase TbCglT, yielding 88.5% of the maximum glucose yield, which was higher than the glucose yield obtained from ammonia-treated rice straw saccharification (59.6%). Moreover, this work presents a new environment-friendly xylanolytic enzyme pretreatment for beneficial hydrolysis of xylan in various agricultural residues, such as rice straw and corn hull. It not only could improve cellulose saccharification but also produced xylose, leading to an improvement of the overall fermentable sugar yields without chemical pretreatment. IMPORTANCE Ongoing research is focused on improving “green” pretreatment technologies in order to reduce energy demands and environmental impact and to develop an economically feasible biorefinery. The present study showed that PcAxy43A, a weak lignin-binding trifunctional xylanolytic enzyme, endoxylanase/β-xylosidase/arabinoxylan arabinofuranohydrolase from P. curdlanolyticus B-6, was capable of conversion of xylan in lignocellulosic biomass such as untreated rice straw to xylose in one step without chemical pretreatment. It demonstrates efficient synergism with endoxylanases PcXyn10C and PcXyn11A to depolymerize xylan in untreated rice straw and enhanced the xylose production and improved cellulose hydrolysis. Therefore, it can be considered an enzymatic pretreatment. Furthermore, the studies here show that glucose yield released from steam- and xylanolytic enzyme-treated rice straw by the combination of CtCel9R and TbCglT was higher than the glucose yield obtained from ammonia-treated rice straw saccharification. This work presents a novel environment-friendly xylanolytic enzyme pretreatment not only as a green pretreatment but also as an economically feasible biorefinery method.